2014
DOI: 10.1017/s1049023x14001046
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Prediction Models for Use of Medical Resources at Urban Auto-racing Events

Abstract: These findings call attention to the need for the development of a versatile and accurate model that can more accurately predict the number of patient encounters and transports associated with mass-gathering events so that medical needs can be anticipated and sufficient resources can be provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…), but also difference in public health systems across countries (leading to different emergency care services delivery policies) hinders extrapolation. This limited generalizability was also confirmed by the 3 studies that applied observations from few mass gatherings to the prediction models of Arbon or Zeitz, showing significant under/overestimation of the medical usage rates when using an existing prediction model [28][29][30]. Future development of prediction models should therefore be validated both internally and externally, preferably against big data sets of various types of mass gatherings.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…), but also difference in public health systems across countries (leading to different emergency care services delivery policies) hinders extrapolation. This limited generalizability was also confirmed by the 3 studies that applied observations from few mass gatherings to the prediction models of Arbon or Zeitz, showing significant under/overestimation of the medical usage rates when using an existing prediction model [28][29][30]. Future development of prediction models should therefore be validated both internally and externally, preferably against big data sets of various types of mass gatherings.…”
Section: Discussionmentioning
confidence: 92%
“…Three studies externally applied prediction models for mass gatherings by comparing the actual number of patient presentations or transports at 3 outdoor electronic dance music manifestations in the USA [28], a US spectator sport manifestations (i.e. automobile race, Baltimore Grand Prix) [29] and a city festival (i.e. Royal Air Show, Adelaide, Australia) [30] with the predicted number by the model developed by Arbon et al [15], by Hartman et al [32] and/or the retrospective (historical) analysis undertaken by Zeitz et al [33].…”
Section: Plos Onementioning
confidence: 99%
“…, 13 , 16 Most of the reviewed manuscripts highlighted the link with temperature and dehydration contributing to a large number of presentations. In comparison, one study suggested that higher temperatures did not affect patient presentations, but rather reduced them 15 . This could be due to alcohol availability, if the events were indoor or outdoor, and the age demographic of the event.…”
Section: Discussionmentioning
confidence: 98%
“…As indicated earlier, the prediction of number of patient encounters during MGs remains complex and somewhat enigmatic as each event has its own characteristics that influence decisions on the deployment of medical resources. 17 Despite these challenges, the results are deemed to hold sufficient confidence because of the different methods the other models used in calculating their predictions. There is a low degree of dependency among the models used.…”
Section: Discussionmentioning
confidence: 99%